Sistem Informasi Penjualan Berbasis Website (Studi Kasus : King’s Distro Kota Sorong): Website Based Sales Information System (Case Study: King’s Distro, Sorong City) - Matheus Supriyanto Rumetna; Tirsa Ninia Lina; Jalminj Tindage; Wiesje Ferdinandus (Jurnal Teknik Informatika, 2024)
King's Distro is a business that operates in the field of selling outfits. In order to continue to develop its business, and maintain its position, especially from business competitors. Innovations to support sales activities must continue to be improved in an effort to increase sales value. One innovation that can be carried out in sales is the existence of a website-based sales information system. The conventional system that was previously running had several obstacles, such as sales which were still centered on certain locations, making it difficult to expand the market reach for sales. The aim of the research is to design and build a website-based sales information system, because this system expands market reach which indirectly increases the number of customers and improves performance. Adobe Dreamweaver CS6, XAMPP and the Mozilla Firefox browser are the tools used in this research. For system development using the Waterfall method. The result is that using a website can make it easier for customers to order or purchase goods because it is more efficient in terms of time and distance. Management of goods sales becomes more accurate and precise because of the computerized system that uses a database as a data storage medium.